Energy-Based Evaluations on Eucalyptus Biomass Production - Thiago L. Romanelli; Marcos Milan; Rafael Cesar Tieppo (International Journal of Forestry Research)
Dependence on finite resources brings economic, social, and environmental concerns. Planted forests are a biomass alternative to the exploitation of natural forests. In the exploitation of the planted forests, planning and management are key to achieve success, so in forestry operations, both economic and noneconomic factors must be considered. This study aimed to compare eucalyptus biomass production through energy embodiment of anthropogenic inputs and resource embodiment including environmental contribution (emergy) for the commercial forest in the Sao Paulo, Brazil. Energy analyses and emergy synthesis were accomplished for the eucalyptus production cycles. It was determined that emergy synthesis of eucalyptus production and sensibility analysis for three scenarios to adjust soil acidity (lime, ash, and sludge). For both, energy analysis and emergy synthesis, harvesting presented the highest input demand. Results show the differences between energy analysis and emergy synthesis are in the conceptual underpinnings and accounting procedures. Both evaluations present similar trends and differ in the magnitude of the participation of an input due to its origin. For instance, inputs extracted from ores, which represent environmental contribution, are more relevant for emergy synthesis. On the other hand, inputs from industrial processes are more important for energy analysis.